Wines and Distillates Through Advertising. Print Marketing Strategies in Argentina and Chile (1900-1930); [Vinos y Destilados a Través de la Publicidad. Estrategias de Marketing Gráfico en Argentina y Chile (1900-1930)] - Lacoste, P (Universidad de Chile, 2019)
This article analyzes the consolidation process of European commercial brands of wines and distillates consolidation in Argentina and Chile, through graphic advertising in Argentinian magazine Caras y Caretas and the Chileans Zigzag and Sucesos, between 1900 and 1930. A purposeful sample of 26 advertisements is examined based upon its significant relevance. The main strategies of the advertising campaigns were identified: the recourse to the aesthetics of Art Nuveau in Bordeaux Wine, Champagne, Cognac, Geneva and Cinzano, and the appeal to the customs of English landowners through Whiskey. It is concluded that the aggressive advertising campaigns managed to shift the symbolic value of traditional statuary consumption: origin and territory of alcoholic beverages, towards the status symbols linked to the culture of the European elite, thus promoting an identity dissociation that only in recent dates It has begun to reverse. © 2019 Authors. All rights reserved.